7=-5+6m

Simple and best practice solution for 7=-5+6m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7=-5+6m equation:


7=-5+6m

We simplify the equation to the form, which is simple to understand
7=-5+6m

We move all terms containing m to the left and all other terms to the right.
-6m=-5-7

We simplify left and right side of the equation.
-6m=-12

We divide both sides of the equation by -06 to get m.
m=2

See similar equations:

| 5(2x-4)=11x+14+9x | | -11=-10+n*16 | | 8.25z=155.5 | | z(2z-3)=17 | | 15w=1.25 | | 19y+5=45-9y | | 10x-20=20x+14 | | -3x+8=-4x+13 | | x^2-kx-3=0 | | 45+3x+10=180 | | 18x-25=11 | | y=2(y/3-1)+5 | | x-62=84 | | y=3ln(3) | | y+19=41 | | M-11.97=-3.97 | | 66=4m-18 | | y=4(y+4)-10 | | 66=4m-8 | | 108+36z=18z-18 | | z-7=47 | | 36=5+15 | | 5y+3*(2+3y)= | | 4cos^2x=5-2sinx | | 1/x-1-1/x-2=2 | | -2(11-x)=5(x+7) | | 2x+5=x^2-6x | | 12+13x+16=5x-51 | | 46+m=100 | | -4(5x+4)=5 | | f(x)=6x-3f(6)-f(2) | | 4y-14=62 |

Equations solver categories